The field and remote sensing analysis of the Kerguelen Archipelago structure, Indian Ocean - MATHIEU, LUCIE (Elsevier, 2011)
The Kerguelen Archipelago is part of an oceanic plateau with a complex history. Little work has been done on the tectonics of the onshore areas, even though the extensive outcrop renders the islands especially good for structural work. We present the results of three field campaigns and remote sensing analysis carried out in the main Kerguelen Island, around Val Travers valley and Mt Ross volcano (Central Plateau) and in the Rallier du Baty peninsula (SW part of the archipelago). We have mapped faults, fracture sets, and the location and geometry of intrusive bodies. We found that the plateau basalt lavas that make up most of the area are densely fractured, crossed by many veins, dykes and some small faults. This work provides a general framework for the structure of Kerguelen Archipelago that is dominated by 110?-striking faults and veins, dyke swarms and an alignment of recent central volcanoes, which have formed in N-S to NNW-SSE directed extensional stress field. The other structures are fractures, veins and dykes which strike 130?-150?, 000? and 030?-050?. They are likely related to transform faults of the Indian oceanic crust and to faults of the north Kerguelen Plateau (offshore basement of the archipelago). These buried structures were likely re-activated by a low magnitude stress field.
PUBLISHED
Keywords: Geology; Tectonics